PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR IPS PESERTA DIDIK MTs. NEGERI 2 LABUHANBATU - Ruslansyah, Ruslansyah Ruslan; Bahri, Bahri Bahri; Marwanting, Marwanting Marwanting; Syawaludiin, Ahmad Syawaluddin Ahmad; Dewi, Andi Dewi Riang Tatai Andi (Universitas Negeri Malang, 2025)
This research aims to determine student learning outcomes in Integrated Social Sciences Subjects by applying the Problem Based Learning (PBL) learning model using PowerPoint media. The type of research is Classroom Action Research (PTK) using qualitative descriptive data analysis techniques. Implementation of actions is carried out through two cycles and each cycle consists of planning, implementation and observation and reflection. The subjects of this research were class IX MTs students. Negeri 2 Labuhanbatu, totaling 32 people, consists of 18 male students and 14 female students. The data collection technique uses a learning outcomes test consisting of a pretest and posttest. The research results obtained showed that the percentage of students' learning completeness that occurred in the pre-cycle was 46.87% and had increased with a completeness percentage of 71.87% in cycle I and increased again to 90.63% in cycle II